Chip budding techniques for walnut (Juglans regia):Enhancing propagation efficiency - Dhiman, Neha; Rohiwala, Paranjay; Dev, Inder (Indian Farming, 2025)
The expansion of walnut cultivation in the country is greatly restricted because of the inadequate supply of quality planting stock from improved varieties and the difficulty in determining the right time for collecting scion wood for budding. Therefore, enhancing propagation methods is essential for the potential growth of the walnut industry. Asexual propagation techniques such as chip budding with 81 per cent success rate are effective for propagating walnuts.Chip budding is vital in walnut propagation because it enhances the efficiency, reliability, and quality of new plant production, ensuring that growers can meet the increasing demand for walnuts with superior cultivars. Its ability to produce uniform, superior-quality, and early-bearing walnut trees makes it an essential practice in modern walnut cultivation. To multiply elite cultivars, it is essential to develop high-quality rootstocks since they boost overall yield and promote early fruiting. Ensuring superior rootstock quality is a key factor in meeting production targets in walnut cultivation.